Measuring biological responses at different levels of organisation to assess the effects of diffuse contamination derived from harbour and industrial activities in estuarine areas. Issue 1 (15th February 2016) - de los Ríos, A.; Pérez, L.; Echavarri-Erasun, B.; Serrano, T.; Barbero, M.C.; Ortiz-Zarragoitia, M.; Orbea, A.; Juanes, J.A.; Cajaraville, M.P.
Abstract: To evaluate the effects of diffuse contamination, biological measurements were applied in a scrap cargo harbour, a marina and an industrial area. Metal accumulation and biomarkers (survival in air, digestive gland and gonad histopathology, lysosomal membrane stability, intralysosomal metal accumulation, transcription of vitellogenin and MT20, peroxisome proliferation and micronuclei formation) were measured in transplanted mussels, together with metrics of benthic invertebrates. Benthic species were classified into ecological groups and univariate indexes were calculated. The marina showed high richness (16) and percentage of opportunistic species (55.1%) and low metal accumulation. Mussels in the scrap cargo harbour showed high metal accumulation, up-regulation of MT20 transcription, reduced health status (LP < 6 min) and increased micronuclei frequencies (up to 11.3‰). At the industrial area, low species richness (4) and badly organised assemblages were detected and chemical analyses indicated significant amounts of bioavailable metals. Overall, selected biological measurements showed potential for the assessment of diffuse contamination. Highlights: Effects of diffuse contamination were assessed on caged mussels and benthic invertebrates. Low exposure to metals and well structured communities were recorded in the marina harbour. Metals available at scrap cargo harbour can be related to micronuclei formation and reduced health. Metal accumulation and poor benthic assemblages were found at the industrial area. Responses at several organisation levels give information on effects at different time scales.